Hematological Markers in Assessing Clinical Characteristics and Disease Severity in Hospitalized Patients with COVID-19: A Single-centric Cross-Sectional Study - Pandey, Sundar; Pokharel, Abhinash (Journal of Karnali Academy of Health Sciences, 2023)
Background: Coronavirus disease is a respiratory illness caused by coronavirus infection. Considering its capability of involving multiple systems showing diverse clinical patterns with complications and death, its needful to recognize reliable predictors of disease severity so that we can allocate the available healthcare facilities and arrange a prompt clinical intervention. This study aims to identify common easily available hematological markers and correlate the clinical severity and outcome. Methods: This observational cross-sectional study was done on 110 COVID-19 RT-PCR-positive patients admitted to the Intensive care unit of Devdaha Medical College. Clinical and laboratory values of hematological parameters like Hemoglobin, leucocyte count, platelets, Neutrophil to lymphocyte ratio, platelets to lymphocyte ratio, and, serum ferritin were recorded from hospital records and case files and analysis was done in relation to disease severity and outcome. Results: Total 110 patients (56 females) were included in this study. The mean age at presentation was 56.5±15.6 years. Fifty-four patients had a chronic disease, the most common were hypertension and diabetes; and complications were high in them (70.38%). The most common complaints were shortness of breath, cough, and fever. Anemia was present in 61.8% of patients, and lymphopenia in 70%. Increased levels of neutrophil to lymphocyte ratio was seen in 93.6% while that of platelets to lymphocyte ratio in 63.64%, and of ferritin in 42.7% of patients. Sixty percent of patients improved with treatment while 11.6% expired during the course of hospital stay. Most of the patients with complications and mortality had deranged hematological markers. Conclusions: Ferritin levels were statistically significant for assessing mortality outcomes. Other common hematological biomarkers like lymphocyte count, platelet to lymphocyte ratio, and neutrophil to lymphocyte ratio could be used for risk stratification and prediction of disease course, identifying vulnerable patients at an early phase of illness, and managing patients as per need.